Ars Educandi. Tom III, 2003, Wydawnictwo Uniwersytetu Gdańskiego, Gdańsk 2003, ss. 284 - Jamrożek, Wiesław (Biuletyn Historii Wychowania, 2003)
Ars Educandi. Tom III, 2003, Wydawnictwo Uniwersytetu Gdańskiego, Gdańsk 2003, ss. 284